Campur Kode dan Interferensi Bahasa Arab di Kampung Condet Jakarta Timur: Kajian Sosiolinguistik - Saputra, Iqbal; Nurhasan, Muhammad; Solihin, Ihin; Khairunnisa, Muthia (Lughaat: Journal of Arabic Linguistics, 2026)
The linguistic phenomenon found in the village of Condet, East Jakarta, especially in border areas, occurs as a result of contact between two languages: the mother tongue and a foreign language, in this case Arabic. Barriers influenced by the use of language (mother tongue) by each language speaker greatly determine the continuity and existence of the mother tongue in border areas. In the context of linguistic communication in bilingual societies, linguistic phenomena such as code-switching, code-mixing, and interference often occur and become the subject of sociolinguistic study. The purpose of this study is to describe the linguistic phenomena of code-mixing and interference and to identify the factors that cause code-mixing and interference in the village of Condet, East Jakarta, through sociolinguistic study. This study uses Muysken's code-mixing theory and Weinreich's interference theory. The method used is a qualitative descriptive method. The data collected are statements from residents of Condet Village, East Jakarta, in the form of words, phrases, and sentences related to code-mixing and interference. The data collection techniques used included observation, interview and documentation. The results of this study indicate that the majority of speakers use code-mixing and interference, but these speakers do not fully understand the correct structure of Arabic. In addition, the majority of speakers in the village of Condet in East Jakarta do not understand the meaning of Arabic expressed in speech.